1983
DOI: 10.2307/529464
|View full text |Cite
|
Sign up to set email alerts
|

Dendrochronological Investigations in the Aegean and Neighboring Regions, 1977-1982

Abstract: Note, please, that figures, notes, and tables have been converted to links and are no longer within the page sequence. For easiest navigation, use the "Back" key to return to the text after accessing these linked figures, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…These are the first chronologies from Kosovo, but there are also some other built earlier in Italy and the Balkan Peninsula. In comparison, the longest nearby P. heldreichii chronologies span periods of 1392 years (617-2008) were found in Albania [14], 762 years (1243 to 2004) in Greece [31], 758 years (1250 to 2008) in Bulgaria [11], and 827 years (1148 to 1974) in Southern Italy [32].…”
Section: Chronology Characteristicsmentioning
confidence: 99%
“…These are the first chronologies from Kosovo, but there are also some other built earlier in Italy and the Balkan Peninsula. In comparison, the longest nearby P. heldreichii chronologies span periods of 1392 years (617-2008) were found in Albania [14], 762 years (1243 to 2004) in Greece [31], 758 years (1250 to 2008) in Bulgaria [11], and 827 years (1148 to 1974) in Southern Italy [32].…”
Section: Chronology Characteristicsmentioning
confidence: 99%
“…In the Byzantine Aegean, examples of historically-dated or inscriptionally-dated buildings with wooden elements that include the bark or an outermost growth ring have demonstrated that the maximum elapsed time between cutting the wood and using it was generally only one year (Kuniholm and Striker, 1987). At Yenikapı, where the vast majority of our samples are oak pilings for docks, there would have been no need to season the wood for any length of time before use.…”
Section: Methodsmentioning
confidence: 97%
“…Such chronologies will contribute to a denser tree-ring network of Bosnian pine, providing a better understanding of the impact of climate on species growth along its geographic range. In comparison, the nearby P. heldreichii chronologies documented for the Balkan Peninsula and southern Italy, span periods of 1392 years (617 to 2008) in Albania [9], 762 years (1243 to 2004) in Greece [25], 758 years (1250 to 2008) in Bulgaria [6] and 827 years (1148 to 1974) in south Italy [26]. The comparison of our chronologies with others from neighbour countries showed a strong dependence on the distance between sampling sites.…”
Section: Discussionmentioning
confidence: 99%